Emotional Arousal at Memory Encoding Enhanced P300 in the Concealed Information Test - Osugi, Akemi; Ohira, Hideki (Frontiers in Psychology, 2018)
Previous studies have reported that the concealed information test (CIT) is a reliable and powerful method for detecting information. However, the external validity of the CIT studies has not been fully proven. In particular, few studies have examined the effects of emotional arousal at memory encoding on physiological responses in the CIT. The present study investigated the influence on the CIT of the magnitude of emotional arousal at memory encoding of a mock crime, using the P300 component of the event-related brain potential (ERP). In accord with the assumptions of excitation-transfer theory, we presented emotionally arousing pictures before a mock crime. Participants were randomly assigned to either a high emotional arousal group (n = 10) or a low emotional arousal group (n = 11), viewing pictures expected to arouse emotion at a high or low level, respectively. Subsequently, all participants enacted the same mock crime, in which they were instructed to stab a pillow with a sharp-edged tool (e.g., a kitchen knife or ice pick) as if harassing a mannequin lying on a bed. After the antecedent emotional experience, the P300-based CIT was conducted. Participants in the high arousal group showed significantly greater P300 amplitudes in response to a probe stimulus compared with the low arousal group. No differences were found between the groups in response to irrelevant stimuli. These results support the notion that emotional arousal influences the P300 in the CIT paradigm.